问题 解答题
脱式计算下面各题
2
3
-(
5
6
-
3
4
)÷
3
8

4
5
÷[(
1
2
+
2
3
)×
4
7
]
5
16
÷
3
4
+
15
16
)×
8
13

[
8
15
-(
4
5
-
3
10
)]×
15
14
答案

(1)

2
3
-(
5
6
-
3
4
)÷
3
8

=

2
3
-
1
12
×
8
3

=

2
3
-
2
9

=

4
9

(2)

4
5
÷[(
1
2
+
2
3
)×
4
7
]

=

4
5
÷[
7
6
×
4
7
]

=

4
5
÷
2
3

=

4
5
×
3
2

=

6
5

(3)(

5
16
÷
3
4
+
15
16
)×
8
13

=(

5
16
×
4
3
+
15
16
)×
8
13

=(

5
12
+
15
16
)×
8
13

=

65
48
×
8
13

=

5
6

(4)[

8
15
-(
4
5
-
3
10
)]×
15
14

=[

8
15
-
1
2
15
14

=

1
30
×
15
14

=

1
28

填空题
单项选择题